THE EFFECTS OF FEEDING WHOLE COTTONSEED AS A SUPPLEMENT FOR SHEEP FED A BASAL DIET GRASS HAY ON FEED DIGESTIBILITY AND THE RUMEN FERMENTATION - . Ismartoyo (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2015)
This experiment was conducted in vivo to investigate the effects of feeding WCS as a supplement for sheep fed GH on the apparent feed digestibility, and the rumen fermentation. Four different diets (T1-T4) were used, GH alone, or GH plus 150, 300 or 500 g WCS d-1 (fresh basis). The main objectives of the in vivo experiment was to examine digestibility and rumen characteristics (pH, ammonia and VFA concentration) of sheep fed the four diets. The results of this experiment indicated that supplementation of GH with WCS at level of 500 g d-1 (0.37 of the diet) reduced DM, ADF and NDF digestibility. There was no statistically significant effect on total rumen VFA, but the molar proportions of acetate, propionate and butyrate were altered by the highest rate of inclusion of WCS. These results suggested that WCS might have reduced the numbers or activities of cellulolytic rumen microorganisms.